Evidence-based practices in autism: where we started to where we are now - Reichow, Brian; Doehring, Peter; Volkmar, Fred (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Autism; Developmental psychology; Psychology; dept.sed

Evidence-based practices and treatments in autism spectrum disorder: concluding thoughts - Volkmar, Fred; Doehring, Peter; Reichow, Brian (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Autism; Autism spectrum disorder; Cognitive psychology; Developmental psychology; Physics; Psychology; Spectrum (functional analysis); dept.sed

Autism spectrum disorder in adolescents and adults: an introduction - Volkmar, Fred R.; Reichow, Brian; McPartland, James C. (Adolescents and Adults with Autism Spectrum Disorders, 2024)
Leo Kanner’s classic description of autism appeared eight decades ago. Although the pace of research has increased dramatically, research specifically focused on adolescents and adults remains limited in many respects. Numerous outcome studies have been conducted and suggest potential for markedly improved outcome with intervention. Unfortunately, studies on adults after early adulthood are sparse and, for old age, almost nonexistent, reflecting a lack of support for research in this population. This is in stark contrast to other developmental disorders in which considerable information on adult life is often available. This book summarizes work across areas, focusing on what is known and not yet known, highlighting important areas for future research. While overall outcome has improved, a small group of individuals remain in need of high levels of adult care. For all individuals, the field requires new approaches to both research and clinical service.
Keywords: Adolescents; Adults; Autism; Outcome; Supports; dept.sed

Practicing Evidence-Based Practices - Eren, Ruth Blennerhassett; Brucker, Pamela Owen (Evidence-Based Practices and Treatments for Children with Autism, 2011)
Public education in the United States has a history of local control in the development of curriculum and instruction. Although notable court decisions have led to more universal applications of educational policy and practices (Brown v. Board of Education 1954, Oberti v. Clementon 1993), it has been federal law that has resulted in significant changes in instruction. The Individuals with Disabilities Education Improvement Act (IDEA; Public Law 108–142), first enacted in Public Law 94–142, guaranteed the right of a free, appropriate public education for all children, regardless of the severity of their disability. The word “appropriate” resulted in the beginning of what we refer to today as differentiated instruction: instructional strategies that allow a child to learn and progress in an educational setting. The federal law, No Child Left Behind (NCLB; Public Law 107-110), enacted in 2001, contributed to this initiative and added a caveat that these differentiated instructional strategies needed to be grounded in scientifically based research. Indeed, the term “scientifically based research” has been noted to appear in NCLB 111 times (Deshler 2002). The federal government, in IDEA 2004, identified 13 eligibility categories. In order to receive special education services, a student must, through a multidisciplinary evaluation, meet the eligibility criteria established for one of the 13 categories. Since 1975, when PL94–142 was enacted, educational interventions for students receiving special education have expanded, particularly in disability categories with a high level of incidence such as speech and language disorders and learning disabilities. Low-incidence disabilities, such as mental retardation, visual impairments, and autism, have received less attention.
Keywords: General Education; Individualize Education Program; Special Education; Special Education Teacher; Team Meeting; dept.sed